A new species of the genus Prethopalpus from Hainan Island, China (Araneae: Oonopidae) - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2013)
Oonopidae are very small (1–3 mm), haplogyne spiders that occur throughout the temperate and tropical regions of the world (Ubick 2005). Recently, a series of papers on the Oonopidae of Hainan Island was published (Tong & Li 2008, 2009, 2010, 2011, 2012). Endowed with a wealth of natural resources that include tropical forests, mountains, mangroves, and beaches, Hainanis recognized as one of the most biologically diverse regions in the world (Ouyang et al. 2001). At present, a total of six genera and 28 species of oonopids have been recorded fromHainan (Platnick 2012).